The Normative Basis of Islamic Astronomy For The Transformation of Prayer Schedules To Digital And Its Accuracy - Rojak, Encep Abdul; Fawzi, Ramdan (El-Usrah: Jurnal Hukum Keluarga, 2024)
The provisions for prayer times have been determined based on the instructions contained in the Qur'an and Sunnah. The Prophet gave an example of starting a prayer time based on the shadow of an object perpendicular to the sun's position relative to the earth. For example, the midday prayer is set when the sun is at its culmination. This shows that the determination of the start of the prayer time is based on the observation of the sun which must be in a certain position for each prayer time. These provisions are transformed into a set of mathematical formulas based on ongoing astronomical observations. In subsequent developments, this prayer schedule will not only be in hard copy form but also in the form of a website and Android application. Several Android applications display the starting schedule for prayers in a place that is different from the others. Every android application that displays prayer times should refer to the initial provisions of the times stipulated in the Shari'a and Fiqh, not limited to mere calculations, nor is there an API which is a common reference for program developers. There needs to be a unified standard calculation system for the android application for prayer times. It is also necessary to make a standard API and Indonesian standards in accordance with the fiqh provisions for the start of prayer times set in Indonesia.